Effect Of Error Augmentation Training Strategy On Engagement In Rehabilitation Therapy - Alexander, Tan Wai Teng (Universiti Sains Malaysia, 2019)
There are numerous strategies in the field of stroke rehabilitation which help to enhance the patients’ engagement in the rehabilitation exercises. One of the most updated strategies for improving an individual’s motor rehabilitation includes a robotic interface known as error augmentation. The goal of this study was to evaluate three error augmentation training strategies (error amplification (EA), random forces disturbances (RD) and training without perturbations (NP)) based on the engagement level during the rehabilitation exercise of healthy individuals. This will form the framework for future application to sub-acute stroke survivors using the developed lower limb stroke rehabilitation system (LLSRS). Five healthy subjects (5 males; age: 22.8 ± 0.45) performed the experiment using the designed LLSRS. The training task consisted of tracking a targeted visual indicator bar presented on a LabVIEW graphic user interface by controlling the amplitude of force applied by the leg. The brain response and sustained engagement of the subject when responding to the different training strategies are studied using electroencephalogram (EEG) obtained from the measured signals of the brain activities based on the Emotiv EPOC+ headset during the exercise. The results demonstrated that the error-augmentation training paradigms can improve the engagement level (p<0.05) in healthy subjects during a rehabilitation exercise compared to conventional rehabilitation therapy. The results also showed that there is no significant difference (p>0.05) between the effectiveness of the training strategies in enhancing the engagement of a subject. A clinical trial will be required to further investigate the efficacy of the rehabilitation treatment using LLSRS in providing similar training advantage to sub-acute stroke patients.